Gender and Climate-relevant Agri-Food Systems Governance: A Strategic Evidence Review - Amoak, Daniel; Najjar, Dina; Kyle, Jordan (International Center for Agricultural Research in the Dry Areas, 2022)
There is a need to address gender inequalities in agri-food systems governance to close the gender gap and improve women's agency and participation in the agri-food sector. Women often face barriers to expressing their voices and exercising their agency in agri-food systems due to a lack of education and knowledge, which limits their ability to adopt and implement new farming techniques for improved yields. Moreso, women are often underrepresented in decision-making processes and leadership roles, which can lead to policies and solutions that do not adequately address their needs and interests. In addition, societal norms and cultural restrictions often limit women's mobility and interactions with men, hindering their participation in productive meetings and decision-making processes. Furthermore, gendered roles and tasks can disincentivize women's involvement in agri-food systems, and traditional practices often favor men in terms of owning agricultural assets such as land. To overcome these barriers, practical approaches such as the diffusion of gender-sensitive technological innovations and the development of women's leadership skills through training can be effective in supporting women's agency in climate-related AFS governance.